Bridging Technology and Pedagogy: A Study on Virtual Academic Supervision for Teacher Professional Growth - Sermal Sermal; Muhammad Yunus (AL-ISHLAH: Jurnal Pendidikan, 2025)
As the digital transformation reshapes education, virtual academic supervision emerges as a promising innovation for teacher professional development. This study explores its effectiveness as an alternative to traditional supervision methods. A systematic literature review (SLR) was conducted, drawing on national and international peer-reviewed journals, reference books, and policy documents. Content analysis and meta-synthesis techniques were applied to synthesize findings and identify best practices in virtual academic supervision. The review reveals that virtual supervision significantly enhances time efficiency by 30–50%, expands the reach of coaching programs, and improves the quality of feedback. Digital platforms—especially learning management systems integrated with video conferencing—receive higher satisfaction ratings compared to conventional methods. Hybrid coaching models that combine synchronous and asynchronous interactions are most effective, offering personalized, flexible learning experiences. Moreover, digital evaluation tools facilitate accurate, data-driven assessments of teacher performance. The study proposes a conceptual framework that integrates technology platforms, coaching strategies, and digital evaluation systems, offering a structured, scalable model for virtual academic supervision. These findings underscore the potential of digital supervision to support sustainable teacher development and call for education policymakers and institutions to adopt this approach as a strategic priority.